Estudio de factibilidad para la creación de una empresa de mujeres cabezas de hogar destinada a producir y a comercializar pijamas (2012)
The proyect presented below outlines the organizational structure, the investment required to carry it out, along with the administrative, financial, economic and technical company. The fashion business has always been concerned to innovate constantly in the garments used by consumers in different types of scenarios, however, have not been precisely pijamas the strongest of these changes, while recognizing that makes significant share of the market, and especially in women. This study allows the company structure by characterizing designs and qualities that will contribute to the final product. Also added is a fundamental idea to make it more attractive as summarized in the employ single mothers for design, cutting and assembly of pijamas, giving an added value to the product and creationg social work at a time. This idea was well received by the target market that is the city of Armenia Q. and more specifically in women 3,4 and 5 layers whose ages are between 18 and 30 years old. The draft will be developed through a satellite clothing. The main reason for using this is that in addition to the low funding to carry it out, mothers can be in charge of their families while they work, what they loved greatly facilitate the conduct activities. Furthermore, it is a note worthy that there has been a sector analysis, with key elements such as costs, competition, the market, the products currently on the market, finance facilities for business creation and last but not least important added value of the product.